A high-performance cross-linked polyolefin cable material and preparation method thereof

By preparing high-performance crosslinked polyolefin cable materials containing phosphorus and nitrogen-free flame retardant, the problems of insufficient flame retardant and flammable existing polyolefin cable materials are solved, and efficient and safe flame retardant and smoke suppression are achieved. and excellent mechanical properties.

CN118515927BActive Publication Date: 2025-01-17RUITIAN CABLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410725277.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-01-17
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

The flame retardant properties of existing polyolefin cable materials are insufficient, flammable and produce droplets and deformation during fire, and high-filled metal inorganic flame retardant leads to poor mechanical and processing performance, and the irradiation crosslinking equipment is high and The environmental hazards are great, and the production cost of silane cross-linking method is high.

Method used

Using a high-performance crosslinked polyolefin cable material preparation method, it is plasticized by mixing low-density polyethylene, inorganic filler, flame retardant, ultraviolet absorber, antioxidant and lubricant after mixing it with a twin-screw extruder. The flame retardant containing phosphorus and nitrogen without halogen-free flame retardant is prepared to improve the flame retardant performance of cable material.

Benefits of technology

It realizes the efficient, safe and stable flame retardant and smoke-retardant effect of cable materials, excellent mechanical properties and anti-aging properties, and the inorganic filler is highly dispersed. The flame retardant and polyvinyl matrix work together to enhance the toughness and resistance of cable materials. Impact strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004878428770000021
    Figure BDA0004878428770000021
  • Figure BDA0004878428770000031
    Figure BDA0004878428770000031
  • Figure BDA0004878428770000032
    Figure BDA0004878428770000032
Patent Text Reader

Abstract

The invention discloses a high-performance cross-linked polyolefin cable material and a preparation method thereof, and belongs to the technical field of cable materials. 10-20 parts of low-density polyethylene, 10-15 parts of inorganic fillers, 3-8 parts of flame retardants, 0.3-0.5 parts of ultraviolet absorbers, 0.3-0.5 parts of antioxidants, and 0.05-0.15 parts of lubricants are mixed; then the masterbatch is plasticized and granulated by a twin-screw extruder; finally, the masterbatch and 90-100 parts of low-density polyethylene are put into a shaking tank, 1.5-2.5 parts of cross-linking agents are added and pressurized, and the cable material is obtained after the cross-linking agent is absorbed. The flame retardant has good compatibility with each raw material, and there is a chemical reaction between polyethylene and the flame retardant, and between the flame retardant and the inorganic filler. Therefore, the flame retardant is highly dispersed and stably present in the cable material, and synergistically acts with each raw material, so that the cable material of the present invention has high efficiency, safety and stable flame retardant and smoke suppression effects, as well as excellent mechanical properties, anti-aging properties, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and in particular relates to a high-performance cross-linked polyolefin cable material and a preparation method thereof. Background Art

[0002] Polyolefins have good dielectric properties, mechanical properties, low temperature resistance, processing properties and chemical stability. Since commercialization, they have been widely used in the production of wires and cables. There are usually three methods for crosslinking polyolefins. The first is the organic peroxide crosslinking method, which uses the decomposition of peroxides to provide free radicals, and then induces CC bonding between polyolefin molecules; the second is the radiation crosslinking method, which uses high-energy rays to trigger free radical formation, similar to peroxide-induced crosslinking, except that the latter CC bond formation is below the crystal melting point; the third is the silane crosslinking method, which first grafts silane crosslinkers on the macromolecular chain, and then hydrolyzes and condenses silanols to form a three-dimensional structure of C-Si-O-Si-C. The radiation crosslinking method has high requirements for cable factory equipment and high equipment purchase costs. At the same time, the radiation generated is more harmful to the environment. The production cost and process requirements of the silane crosslinking method are also high.

[0003] In addition, since cross-linked polyolefin itself has a low oxygen index and is a flammable material, when there is an external fire source or an internal fault, the cross-linked polyolefin cable is very likely to burn and cause a fire. In order to improve the flame retardant properties of polyolefin cable materials, the use of smoke-suppressing, non-toxic hydrated metal compound inorganic flame retardants such as aluminum hydroxide and magnesium hydroxide has recently become the main direction to improve the flame retardant properties of polyolefin. However, the flame retardant polyolefin cable material with only inorganic flame retardants has a droplet phenomenon when burning, and has deformation problems when heated. In addition, the high filling of metal hydroxides will lead to poor mechanical and processing properties. Therefore, it is urgent to design a high-performance cross-linked polyolefin cable material. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-performance cross-linked polyolefin cable material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing a high-performance cross-linked polyolefin cable material comprises the following steps:

[0007] 10-20 parts of low-density polyethylene, 10-15 parts of inorganic filler, 3-8 parts of flame retardant, 0.3-0.5 parts of ultraviolet absorber, 0.3-0.5 parts of antioxidant and 0.05-0.15 parts of lubricant are put into a high-speed mixer and mixed for 5-10 minutes; then the mixed raw materials are plasticized and granulated by a 160°C twin-screw extruder to obtain master batches; finally, the master batches and 90-100 parts of low-density polyethylene are put into a 80-90°C shaking tank, 1.5-2.5 parts of cross-linking agent are added and pressurized to 0.2MPa, and the cross-linking agent is absorbed by penetration to prepare a cross-linked polyolefin cable material.

[0008] Furthermore, the inorganic filler is one or both of magnesium hydroxide and aluminum hydroxide.

[0009] Furthermore, the flame retardant is prepared by the following steps:

[0010] S1. First, blow nitrogen gas into a dry three-necked flask for 30 minutes, then add 2,4,5-trichloropyrimidine, N-methylallylamine, triethylamine and toluene, stir to dissolve, heat to 80°C and react for 4 hours. After the reaction is completed, cool to room temperature and distill under reduced pressure to obtain intermediate 1; the dosage ratio of 2,4,5-trichloropyrimidine, N-methylallylamine, triethylamine and toluene is 8.6mL:7.2mL:23mL:180mL.

[0011] Under the action of triethylamine, the molar ratio of 2,4,5-trichloropyrimidine and N-methylallylamine is controlled to be 1:1, and a -Cl of 2,4,5-trichloropyrimidine and -NH- of N-methylallylamine undergo nucleophilic substitution reaction. The reaction process is as follows:

[0012]

[0013] S2. The dry brown three-necked flask was purged with nitrogen for 30 minutes, and then γ-mercaptopropyltrimethoxysilane, sodium hydroxide and dimethyl sulfoxide were added, stirred thoroughly, and then the intermediate 1 and potassium iodide were slowly added. After the addition was completed, the temperature was raised to 105°C and stirred for reaction for 4 hours. After the reaction was completed, it was cooled to room temperature and distilled under reduced pressure. The mixture was washed with anhydrous ethanol for 5 times, dried at 80°C for 6 hours, purified by column chromatography (the eluent was a mixed solvent of chloroform and ether, and the volume ratio of chloroform and ether was 9:1), and distilled under reduced pressure. The whole process was carried out under nitrogen protection to obtain intermediate 2; the amount ratio of γ-mercaptopropyltrimethoxysilane, intermediate 1, sodium hydroxide, potassium iodide and dimethyl sulfoxide was 8.6mL:8.7g:1.8g:1.3g:130mL.

[0014] Under the catalysis of potassium iodide and alkaline conditions, when the molar ratio of intermediate 1 to γ-mercaptopropyltrimethoxysilane is 1:1.1-1.2, -Cl of intermediate 1 and -SH of γ-mercaptopropyltrimethoxysilane undergo nucleophilic substitution reaction, and the reaction process is as follows:

[0015]

[0016] S3. First, blow nitrogen gas into a dry three-necked flask for 30 minutes, then add intermediate 2, didodecylamine, triethylamine and dimethyl sulfoxide, stir to dissolve, then heat to 90°C, keep warm for 12 hours, cool to room temperature after the reaction, and distill under reduced pressure to obtain intermediate 3; the amount ratio of intermediate 2, didodecylamine, triethylamine and dimethyl sulfoxide is 13.2g:13.6g:9.7mL:200mL.

[0017] Under the action of triethylamine, the molar ratio of intermediate 2 and didodecylamine is controlled to be 1:1.05-1.2, and a -Cl of intermediate 2 and -NH- of 1-tetradecanol undergo nucleophilic substitution reaction. The reaction process is as follows:

[0018]

[0019] S4. Under nitrogen protection, the intermediate 3, 2-diethoxyphosphorylethanol, tetraisopropoxytitanium and N,N-dimethylformamide were stirred and mixed for 0.5h, then heated to 90°C and stirred for 24h. After the reaction, the mixture was cooled to room temperature, distilled under reduced pressure, washed with anhydrous ethanol 5 times, dried at 80°C for 6h, purified by column chromatography (the eluent was a mixed solvent of ethyl acetate and petroleum ether, with a volume ratio of ethyl acetate and petroleum ether of 1:2), and distilled under reduced pressure. The whole process was carried out under nitrogen protection to obtain a flame retardant. The dosage ratio of intermediate 3, 2-diethoxyphosphorylethanol, tetraisopropoxytitanium and N,N-dimethylformamide was 17.4g:4.9g:0.25g:230mL.

[0020] The molar ratio of intermediate 3 and 2-diethoxyphosphorylethanol is controlled to be 1:1.05-1.1. Then, under the catalytic action of tetraisopropoxytitanium, a silaneoxy group of intermediate 3 and a hydroxyl group of 2-diethoxyphosphorylethanol undergo the following chemical reaction. The reaction process is shown below:

[0021]

[0022] The flame retardant of the present invention contains phosphorus and nitrogen halogen-free flame retardant elements, which work synergistically, so that the flame retardant of the present invention has an efficient and safe flame retardant effect; the flame retardant of the present invention contains aromatic heterocycles and long carbon chains, and according to similar compatibility, the flame retardant of the present invention has good compatibility with other raw materials; the long carbon chain (12 carbons) in the flame retardant that can freely expand and rotate can be inserted into the polyethylene macromolecular chain, which enhances the toughness and impact strength of the cable material to a certain extent; under the action of the crosslinking agent, the double bonds in the flame retardant can react chemically with the unreacted carbon-carbon double bonds in the matrix resin, that is, the linear low-density polyethylene, and then be grafted onto In polyethylene, therefore, the flame retardant can be further dispersed in the cable material. At the same time, the chemical action enables it to stably exist in the cable material and will not migrate or escape due to the influence of the external environment, giving full play to the stable flame retardant effect; the flame retardant also contains silaneoxy, which is easily hydrolyzed and condensed, and then produces covalent bonds with the hydroxyl groups on the surface of the inorganic filler to form a chemical force, thereby greatly reducing the surface energy of the inorganic filler, making the inorganic filler highly dispersed in the cable material, and synergistically exerting the flame retardant and smoke suppression effect with the flame retardant. This chemical force also promotes the high dispersion of the flame retardant, further promoting the full play of the flame retardant effect of the flame retardant.

[0023] Furthermore, the ultraviolet absorber is one or more of ultraviolet absorber UV-P, ultraviolet absorber UV-9, ultraviolet absorber UV-531, and ultraviolet absorber UV-327.

[0024] Furthermore, the antioxidant is one or more of tetrakis-[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol, 4,4'-thiobis(6-tert-butyl-m-cresol), and tris(2,4-di-tert-butylphenyl) phosphite.

[0025] Furthermore, the lubricant is one or more of erucamide, ethylene bisstearamide, stearic acid, polyethylene wax, and paraffin.

[0026] Furthermore, the cross-linking agent is dicumyl peroxide.

[0027] The invention also discloses a high-performance cross-linked polyolefin cable material, which is prepared according to the preparation method of the high-performance cross-linked polyolefin cable material.

[0028] Beneficial effects of the present invention: the flame retardant containing multiple long carbon chains (12 carbons) has good compatibility with other raw materials, and there is a chemical reaction between polyethylene and the flame retardant, and between the flame retardant and the inorganic filler. Therefore, the flame retardant containing phosphorus and nitrogen halogen-free flame retardant elements is highly dispersed and stably present in the cable material, and acts synergistically with the raw materials. Therefore, the cable material of the present invention has efficient, safe and stable flame retardant and smoke suppression effects as well as excellent and stable mechanical properties, anti-aging properties, etc. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] The flame retardant is prepared in the following specific steps:

[0032] S1. First, blow nitrogen gas into a dry 500 mL three-necked flask for 30 min, then add 8.6 mL of 2,4,5-trichloropyrimidine, 7.2 mL of N-methylallylamine, 23 mL of triethylamine and 180 mL of toluene, stir to dissolve, heat to 80 ° C and react for 4 h. After the reaction is completed, cool to room temperature and distill under reduced pressure to obtain intermediate 1;

[0033] S2, a dry 250mL brown three-necked flask was purged with nitrogen for 30min, and then 8.6mL γ-mercaptopropyltrimethoxysilane, 1.8g sodium hydroxide and 130mL dimethyl sulfoxide were added, and the mixture was stirred thoroughly. Then 8.7g intermediate 1 and 1.3g potassium iodide were slowly added. After the addition was completed, the mixture was heated to 105°C and stirred for 4h. After the reaction was completed, the mixture was cooled to room temperature, and distilled under reduced pressure. The mixture was washed with anhydrous ethanol for 5 times, dried at 80°C for 6h, purified by column chromatography (a mixed solvent of chloroform and ether was used as the eluent, and the volume ratio of chloroform to ether was 9:1), and distilled under reduced pressure. The whole process was carried out under nitrogen protection to obtain intermediate 2;

[0034] S3, first purging a dry 250mL three-necked flask with nitrogen for 30min, then adding 13.2g of intermediate 2, 13.6g of didodecylamine, 9.7mL of triethylamine and 200mL of dimethyl sulfoxide, stirring and dissolving, heating to 90°C, keeping the temperature for reaction for 12h, cooling to room temperature after the reaction is completed, and distilling under reduced pressure to obtain intermediate 3;

[0035] S4. Under nitrogen protection, 17.4 g of intermediate 3, 4.9 g of 2-diethoxyphosphorylethanol, 0.25 g of tetraisopropoxytitanium and 230 mL of N,N-dimethylformamide were stirred and mixed for 0.5 h, then heated to 90 ° C and stirred for reaction for 24 h. After the reaction, it was cooled to room temperature, distilled under reduced pressure, washed with anhydrous ethanol 5 times, dried at 80 ° C for 6 h, purified by column chromatography (the eluent was a mixed solvent of ethyl acetate and petroleum ether, and the volume ratio of ethyl acetate and petroleum ether was 1:2), and distilled under reduced pressure. The whole process was carried out under nitrogen protection to obtain a flame retardant.

[0036] Example 2

[0037] The specific steps for preparing cross-linked polyolefin cable materials are as follows:

[0038] First, 10 parts of low-density polyethylene, 10 parts of aluminum hydroxide, 3 parts of the flame retardant of Example 1, 0.3 parts of ultraviolet absorber UV-P, 0.3 parts of tetrakis-[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester, and 0.05 parts of ethylene bisstearamide are put into a high-speed mixer and mixed for 5 minutes; then the mixed raw materials are plasticized and granulated by a 160°C twin-screw extruder to obtain a masterbatch; finally, the masterbatch and 90 parts of low-density polyethylene are put into an 80°C shaking tank, 1.5 parts of diisopropyl peroxide are added and pressurized to 0.2MPa, and after the cross-linking agent is infiltrated and absorbed, a cross-linked polyolefin cable material can be prepared.

[0039] Example 3

[0040] Preparation of cross-linked polyolefin cable material, the specific steps are as follows:

[0041] First, 18 parts of low-density polyethylene, 13 parts of magnesium hydroxide, 7 parts of the flame retardant of Example 1, 0.4 parts of ultraviolet absorber UV-531, 0.2 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid octadecyl alcohol, 0.2 parts of 4,4'-thiobis(6-tert-butyl-m-cresol), and 0.12 parts of erucamide are put into a high-speed mixer and mixed for 8 minutes; then the mixed raw materials are plasticized and granulated by a 160°C twin-screw extruder to obtain a masterbatch; finally, the masterbatch and 95 parts of low-density polyethylene are put into an 85°C shaking tank, 2.1 parts of diisopropyl peroxide are added and pressurized to 0.2MPa, and after the cross-linking agent is infiltrated and absorbed, a cross-linked polyolefin cable material can be prepared.

[0042] Example 4

[0043] The specific steps for preparing cross-linked polyolefin cable materials are as follows:

[0044] First, 20 parts of low-density polyethylene, 10 parts of magnesium hydroxide, 5 parts of aluminum hydroxide, 8 parts of the flame retardant of Example 1, 0.5 parts of ultraviolet absorber UV-327, 0.3 parts of tetrakis-[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester, 0.2 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.15 parts of polyethylene wax are put into a high-speed mixer and mixed for 10 minutes; then the mixed raw materials are plasticized and granulated by a 160°C twin-screw extruder to obtain a masterbatch; finally, the masterbatch and 100 parts of low-density polyethylene are put into a 90°C shaking tank, 2.5 parts of diisopropyl peroxide are added and pressurized to 0.2MPa, and after the cross-linking agent is infiltrated and absorbed, a cross-linked polyolefin cable material can be prepared.

[0045] Comparative Example 1

[0046] The specific steps for preparing cross-linked polyolefin cable materials are as follows:

[0047] The remaining steps remain unchanged, only the flame retardant in Example 5 is removed to prepare a cross-linked polyolefin cable material.

[0048] Comparative Example 2

[0049] The specific steps for preparing cross-linked polyolefin cable materials are as follows:

[0050] The remaining steps remain unchanged, and the flame retardant in Example 5 is replaced by 3-[(hydroxymethyl)amino]-3-oxopropylphosphonic acid-dimethyl ester to prepare a cross-linked polyolefin cable material.

[0051] Performance Testing

[0052] The cable materials prepared in Examples 2-4 and Comparative Examples 1-2 were subjected to the following performance tests:

[0053] The limiting oxygen index (LOI) test refers to GB / T2406, and the sample size is 130×6.5×3mm 3 ;Vertical burning test UL-94 refers to GB / T2408-2008, cable material sample size is 100×13×3mm 3 , according to the duration of the flame of the sample, the UL-94 grade is divided into V-0, V-1, V-2 and no grade (indicated by "-"); the maximum smoke density of the cable material is measured according to the standard ASTM E662; the tensile strength and elongation at break are tested using a WDW-20G universal mechanical testing machine, the test refers to GB / T1040.3-2006, and the tensile rate is 10mm / min; the test results of all items are shown in the following table:

[0054] project LOI / % UL-94 Tensile strength / MPa Elongation at break / % Maximum smoke density Example 2 34.1 V-0 16.5 456 51 Example 3 34.5 V-0 16.6 458 50 Example 4 34.7 V-0 16.8 461 50 Comparative Example 1 27.9 - 15.2 442 112 Comparative Example 2 30.4 V-0 15.3 444 65

[0055] It can be seen from the above table that the cross-linked polyolefin cable material prepared in the embodiment of the present invention has excellent flame retardant and smoke suppression effects and mechanical properties.

[0056] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0057] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-performance cross-linked polyolefin cable material, characterized in that: The following steps are involved: 10-20 parts of low-density polyethylene, 10-15 parts of inorganic filler, 3-8 parts of flame retardant, 0.3-0.5 parts of ultraviolet absorber, 0.3-0.5 parts of antioxidant, and 0.05-0.15 parts of lubricant are mixed by weight; then plasticized and granulated by a twin-screw extruder to obtain masterbatch; finally, the masterbatch and 90-100 parts of low-density polyethylene are put into a shaking tank, 1.5-2.5 parts of cross-linking agent are added and pressurized, and the cross-linking agent is absorbed to obtain a cross-linked polyolefin cable material; Wherein, the flame retardant is prepared by the following steps: S1. Add 2,4,5-trichloropyrimidine, N-methylallylamine, triethylamine and toluene into a flask with nitrogen, stir, heat to 80°C, react for 4 hours, cool, and distill under reduced pressure to obtain intermediate 1; the dosage ratio of 2,4,5-trichloropyrimidine, N-methylallylamine, triethylamine and toluene is 8.6 mL:7.2 mL:23 mL:180 mL; S2, nitrogen purged the flask, added γ-mercaptopropyltrimethoxysilane, sodium hydroxide and dimethyl sulfoxide, stirred, added intermediate 1 and potassium iodide, heated to 105 ° C for 4 hours, cooled, distilled under reduced pressure, washed, dried, purified by column chromatography, and distilled under reduced pressure to obtain intermediate 2; the amount ratio of γ-mercaptopropyltrimethoxysilane, intermediate 1, sodium hydroxide, potassium iodide and dimethyl sulfoxide is 8.6mL:8.7g:1.8g:1.3g:130mL; S3, nitrogen purged flask, added intermediate 2, didodecylamine, triethylamine and dimethyl sulfoxide, stirred, heated to 90 ° C for 12 hours, cooled, and distilled under reduced pressure to obtain intermediate 3; the amount ratio of intermediate 2, didodecylamine, triethylamine and dimethyl sulfoxide was 13.2g:13.6g:9.7mL:200mL; S4. Under nitrogen protection, the intermediate 3, 2-diethoxyphosphorylethanol, tetraisopropoxytitanium and N,N-dimethylformamide are mixed, the temperature is raised to 90°C for reaction for 24 hours, cooled, distilled under reduced pressure, washed, dried, purified by column chromatography, and distilled under reduced pressure to obtain a flame retardant; the amount ratio of the intermediate 3, 2-diethoxyphosphorylethanol, tetraisopropoxytitanium and N,N-dimethylformamide is 17.4g:4.9g:0.25g:230mL.

2. The method for preparing a high-performance cross-linked polyolefin cable material according to claim 1, characterized in that: The inorganic filler is one or both of magnesium hydroxide and aluminum hydroxide.

3. The method for preparing a high-performance cross-linked polyolefin cable material according to claim 1, characterized in that: The ultraviolet absorber is one or more of the ultraviolet absorber UV-P, ultraviolet absorber UV-9, ultraviolet absorber UV-531, and ultraviolet absorber UV-327.

4. The method for preparing a high-performance cross-linked polyolefin cable material according to claim 1, characterized in that: The antioxidant is one or more of tetrakis-[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, 4,4'-thiobis(6-tert-butyl-m-cresol), and tris(2,4-di-tert-butylphenyl) phosphite.

5. The method for preparing a high-performance cross-linked polyolefin cable material according to claim 1, characterized in that: The lubricant is one or more of erucic acid amide, ethylene bis stearamide, stearic acid, polyethylene wax and paraffin; the cross-linking agent is dicumyl peroxide.

6. A high-performance cross-linked polyolefin cable material, characterized in that: The high-performance cross-linked polyolefin cable material is prepared according to the preparation method of any one of claims 1 to 5.

Citation Information

Patent Citations

  • Halogen-free flame retardant irradiation-crosslinked cable material and preparation method thereof

    CN106554574A

  • PE cable sheath material with good flame retardant effect and preparation method thereof

    CN116656027A